Prevalência de Porphyromonas gingivalis, genótipo fima II de Porphyromonas gingivalis e Aggregatibacter actinomycetemcomitans em indivíduos com periodontite agressiva generalizada - Rodrigues, Richelle Soares (2014)
Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans are periodontal pathogens associated with aggressive periodontitis. The fimbriae, a structure related to adhesion and invasion of cells, is one of the major virulence factors of P. gingivalis. Based on the nucleotide sequence, six genotypes(fimA) encoding the major fimbriae of these bacteria were identified, and the fimA II is the most commonly associated with periodontal destruction. The objective of this study was to evaluate, by polymerase chain reaction in subgingival plaque samples from sites with highest probing depth in patients with aggressive periodontitis, the prevalence of P. gingivalis, P. gingivalis genotype fimA II and A. actinomycetemcomitans, and relate the presence of these pathogens or genotype to age and clinical periodontal parameters (plaque index, gingival bleeding index, probing depth and clinical attachment level) in these patients. We selected 45 patients with generalized aggressive periodontitis, aged from 15 to 40 years. 64.4% of these patients harbored P. gingivalis and 28.8% harbored A. actinomycetemcomitans in their subgingival microbiota. In patients positive for P. gingivalis, 82.6 % presented the genotype fimA II. In relation to the presence or absence of bacteria or gene to clinical data and age, a statistically significant difference between clinical attachment level was observed in the selected sites of patients with the presence of P. gingivalis and its genotype fimA II when compared to patients negative for these bacteria and genotype, with periodontal loss significantly higher in patients harboring P. gingivalis and in patients harboring genotype fimA II. In addition, the average age in patients positives for P. gingivalis was significantly higher than in negative ones. It is therefore concluded that P. gingivalis and its genotype fimA II are present in high prevalence in patients with aggressive periodontitis, A. actinomycetemcomitans is present in a smaller proportion of individuals in the studied population and P. gingivalis seems to be more commonly found in deeper sites and older individuals.